Rotating Disk Apparatus: Types, Developments and Future Applications - Rashed, K. Musaab; Abdulbari, Hayder A.; Mohamad Amran, Mohd Salleh; M. Halim Shah, Ismail (Canadian Center of Science and Education, 2016)

(untitled)
Power consumption reduction investigations attracted the attention of enormous numbers of researchers in the past few decades due to its high academic and economic impacts. The pumping power losses during the transportation of crude oils are considered as one of the main power consuming applications due to the turbulent mode of transportation. Investigating the possible solutions for this problem is expensive and time consuming due to the large apparatuses needed to simulate the flow in real pipelines. Rotating disk apparatus (RDA) is an instrument mainly comprising a rotating disk and an electrical motor to rotate the disk, which was implemented as an efficient and economical path to simulate what can be done in pipelines through generating a controlled degree of turbulence. This technique was also used in many other scientific applications due to its dynamic mode of operation. For example, a rotating disk electrode was used in electrodeposition processes and to characterize deposition film thickness and uniformity. The rotating disk reactor was employed to investigate the reaction rate between fluids and solid surfaces. The present work evaluates the RDA from different prospective and applications in order to introduce it as an efficient research tools for future dynamic investigations.